Direct Marketing Channel - Gliceria, Gómez-Ceballos; Dalton, Orellana-Quezada; Javier, Samaniego-Astudillo (Journal of Ecohumanism, 2025)
The teaching-learning process is integrated with practice to meet the demands of the labor market. This study presents the learning experience of students at Universidad Politécnica Salesian (UPS), Ecuador, and their contribution to territorial development through an integrated commercialization proposal. This initiative connects eight rural productive associations from El Valle Parish, Cuenca, Ecuador, with the university. It highlights how knowledge transfer drives proposals aligned with agricultural policies, particularly the promotion of direct marketing channels. A mixed-methods approach was adopted: a quantitative methodology was used for production data collection, market segment profiling, and hypothesis testing; while a qualitative approach, through participatory action research, allowed students to develop skills by interacting with project participants and focusing on solutions to local challenges. Data collection was conducted through surveys, interviews, and focus groups, enabling the identification of producers’ and consumers’ needs while also fostering key competencies in students to address challenges in the agri-food sector. The results demonstrate the potential of higher education to generate sustainable solutions for local communities. The results obtained demonstrate the potential of higher education to generate sustainable solutions and a positive impact on local communities.